The effect of social exclusion on consumer preference for anthropomorphized brands1. Issue 1 (25th May 2016) - Chen, Rocky Peng; Wan, Echo Wen; Levy, Eric
Abstract: Prior research has mainly examined the effect of social exclusion on individuals' interactions with other people or on their product choices as an instrument to facilitate interpersonal connection. The current research takes a novel perspective by proposing that socially excluded consumers would be more motivated to establish a relationship with a brand (rather than using the brand to socially connect with other people) when the brand exhibits human‐like features. Based on this premise, we predict and find support in three studies that socially excluded consumers, compared with non‐excluded consumers, exhibit greater preference for anthropomorphized brands (studies 1–3). This effect is mediated by consumers' need for social affiliation and is moderated by the opportunity for social connection with other people (study 2). Furthermore, socially excluded consumers differ in the types of relationships they would like to build with anthropomorphized brands, depending on their attributions about the exclusion. Specifically, consumers who blame themselves (others) for being socially excluded show greater preference for anthropomorphized partner (fling) brands (study 3).